Penyebab Kerusakan Electro Motor Oil Max Pump pada Mesin Induk di KM. Dharma Kartika IX - Andi Hendrawan; Siswadi Siswadi; Supari Supari; Ragil Ajun Abdilah Al Khomsi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2021)
Penggunaan The use of pumps is mostly as a driver, conveyor, press machine, elevator and others. Induction motors are most widely used because they are strong, crowing and easy to maintain and their efficiency at power is high. The problems that often occur in each electro motor are mechanical damage, such as over-current, mechanical failure, low insulation resistance, insufficient lubrication, excessive vibration, misalignment, motor age and other factors. operation of the induction motor, data obtained through Field Research research direct observation of the object under study. The research was conducted by means of observation on the KM Dharma Kartika IX. Based on the research results that the cause of damage to the electro motor components is caused by several things: overcurrent, mechanical damage, low insulation resistance and excess heat.